Evapotranspiration Partitioning and Response to Abnormally Low Water Levels in a Floodplain Wetland in China - Xiaosong Zhao; Yuanbo Liu (Advances in Meteorology)
Evapotranspiration (ET) is an important component of the wetland water budget. Water level declines in Poyang Lake, the largest freshwater lake in China, have caused concerns, especially during low water levels. However, how wetland ET and its partitioning respond to abnormally low water levels is unclear. In this study, wetland ET was estimated with MODIS data and meteorological data. The wetland ET partitioning and its relationship with abnormally low water levels were analyzed for 2000–2013. The results showed that the water evaporation rate (Ewater) was larger than the land ET rate (ETland); the ETland/Ewater ranged from 0.77 to 0.99. When the water level was below 12.8 m, the ET partition ratio was larger than 1, which indicates that wetland ET comes from land surface ET more than water evaporation. The negative standardized water level index (SWI) was used to represent an abnormally low water level in the wetland. Although the monthly wetland ET decreased as the negative SWI decreased, ETland was higher than the average under negative SWI conditions from September to December, when the water level decreased. The abnormally low water level induced more water loss from the land surface, especially when the water level decreased, which reduced the available water resources along the wetland shore.